2021
DOI: 10.1155/2021/6656092
|View full text |Cite
|
Sign up to set email alerts
|

Potential Predictors of Poor Prognosis among Severe COVID-19 Patients: A Single-Center Study

Abstract: Background. Timely detection of the progression of the highly contagious coronavirus disease (COVID-19) is of utmost importance for management and intervention for patients in intensive care (ICU). Aim. This study aims to better understand this new infection and report the changes in the various laboratory tests identified in critically ill patients and associated with poor prognosis among COVID-19 patients admitted to the ICU. Methods. This was a retrospective study that included 160 confirmed SARS-CoV-2-posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Increasing age and multiple comorbidities are known risk factors for severe disease and unfavourable outcomes. [ 2 , 21 - 23 ] We found that patients who progressed to severe disease were older, male, and more likely to have CKD ( P = .0021) as a comorbidity. Similarly, another study found that increased age, male gender, and CKD had a prognostic value for mortality and/or severe disease in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 83%
“…Increasing age and multiple comorbidities are known risk factors for severe disease and unfavourable outcomes. [ 2 , 21 - 23 ] We found that patients who progressed to severe disease were older, male, and more likely to have CKD ( P = .0021) as a comorbidity. Similarly, another study found that increased age, male gender, and CKD had a prognostic value for mortality and/or severe disease in COVID-19 patients.…”
Section: Discussionmentioning
confidence: 83%
“…There has not been any additional research from Saudi Arabia to ascertain whether there is a correlation between the patient’s characteristics and intubation and mortality. Therefore, being aware of these differences can aid in predicting which cases of COVID-19 will require intubation and can have higher chances of mortality, consequently improving the overall efficacy of case management [ 30 , 31 , 32 , 33 ]. This awareness also facilitates the development of preventative actions, the identification of COVID-19′s impact on hospital capacity, and the enhancement of patient bed capacity and healthcare systems through risk classification.…”
Section: Introductionmentioning
confidence: 99%
“…The causative agent was a novel coronavirus called severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The SARS-CoV-2 belongs to a class of single-stranded RNA viruses, beta coronaviruses of the family Coronaviridae, and has a long incubation period with human-to-human transmission (Ghaith M et al,2021). Though the symptoms were usually mild to moderate, in the early stages, patients developed acute respiratory symptoms, and few developed acute respiratory failure and other serious complications (Zheng J et al, 2020) In the case of mild to moderate cases symptomatic treatment and isolation are required, but in severe patients, Intensive Care Unit (ICU) admission is required.…”
Section: Introductionmentioning
confidence: 99%